2019
DOI: 10.1002/cbf.3447
|View full text |Cite
|
Sign up to set email alerts
|

Promotion effects of mono‐2‐ethyhexyl phthalate (MEHP) on migration and invasion of human melanoma cells via activation of TGF‐β signals

Abstract: Malignant melanoma is one of the most leading forms of skin cancer associated with a low patient survival rate. There is an urgent need to illustrate risk factors that can trigger the motility of melanoma cancer cells. Our present study revealed that mono-(2ethylhexyl)phthalate (MEHP) exposure can significantly increase the in vitro migration and invasion of WM983A and A375 cells. Among the tested cytokines, MEHP can increase the expression of transforming growth factor β (TGF-β). Inhibition of TGF-β via its n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 42 publications
(47 reference statements)
0
5
0
Order By: Relevance
“…RES has the potential to suppress EMT via TGF-b1/Smads signaling, as proved by the up-regulating of E-cadherin and the downregulating of Snail and vimentin (16). Snail, a TGF-b1/Smad signaling pathway modulated gene (111,112), restrains the Ecadherin expression and triggers the EMT process (16). Furthermore, they also found that with the treatment of RES, TGF-b1-induced MMP2 and MMP9 decreased through expression analysis (16).…”
Section: Colorectal Cancermentioning
confidence: 96%
“…RES has the potential to suppress EMT via TGF-b1/Smads signaling, as proved by the up-regulating of E-cadherin and the downregulating of Snail and vimentin (16). Snail, a TGF-b1/Smad signaling pathway modulated gene (111,112), restrains the Ecadherin expression and triggers the EMT process (16). Furthermore, they also found that with the treatment of RES, TGF-b1-induced MMP2 and MMP9 decreased through expression analysis (16).…”
Section: Colorectal Cancermentioning
confidence: 96%
“…Synthetic surfactants can inhibit cell migration. Effective results were achieved by testing mono-2-ethyhexyl phthalate (MEPH) in the presence of A375 cells [38]. Compared to the commonly used chemotherapeutic agent ciprofloxacin, the results obtained from the wound healing assay are similar [39].…”
Section: Migration-scratch Assaymentioning
confidence: 99%
“…2) [79][80][81]. During cancer progression, tumor cells active the TGF-β pathway to mediate tumor growth, invasion, and metastasis [82]. TGF-β is a crucial mediator for FOXP3 in tumor infiltrating Tregs.…”
Section: Tumor and Treg Cell Contact Mechanismsmentioning
confidence: 99%